2018
DOI: 10.1016/j.jpain.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Alternating Current Stimulation at Alpha Frequency Reduces Pain When the Intensity of Pain is Uncertain

Abstract: To our knowledge, this is the first study to suggest that somatosensory alpha tACS might lead to a reduction in pain. Interventions targeting alpha activity may have the potential to alleviate chronic pain. However, a patient's expectation about the intensity of upcoming pain must also be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 64 publications
2
51
0
1
Order By: Relevance
“…However, where this study only included brief periods of stimulation, Ahn et al applied alpha tACS for 40 minutes. In an experimental pain setting with pain-free volunteers, Ecsy et al (2018; achieved a significant reduction in pain ratings using 10 minutes of auditory and visual stimulation and Arendsen et al (2018) applied alpha tACS for 15-20 minutes. This feasibility study focused primarily on the entrainment of alpha activity, where it has been shown that even very short periods of stimulation can entrain alpha oscillations (Herrmann 2001;Mathewson et al 2012;.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, where this study only included brief periods of stimulation, Ahn et al applied alpha tACS for 40 minutes. In an experimental pain setting with pain-free volunteers, Ecsy et al (2018; achieved a significant reduction in pain ratings using 10 minutes of auditory and visual stimulation and Arendsen et al (2018) applied alpha tACS for 15-20 minutes. This feasibility study focused primarily on the entrainment of alpha activity, where it has been shown that even very short periods of stimulation can entrain alpha oscillations (Herrmann 2001;Mathewson et al 2012;.…”
Section: Discussionmentioning
confidence: 99%
“…Camfferman et al 2017), the functional role of alpha activity in the perception of chronic pain remains unclear. Experimental pain studies have demonstrated that the relationship between alpha activity and pain is influenced by attention (Hauck et al 2015;May et al 2012) and expectations about pain (Huneke et al 2013;Arendsen, Hugh-Jones, and Lloyd 2018), and that pain expectations can influence the effect of neuro-stimulation on pain perception (Arendsen, Hugh-Jones, and Lloyd 2018). However, the relationship between attention, expectation, and alpha activity in a setting of chronic pain is little understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of tACS on other sensory modalities, including audition [5] and pain [14], have been reported. Most relevant here, however, is how tACS stimulation may influence somatosensation.…”
mentioning
confidence: 99%
“…Nonetheless, the current findings invite more robust and comprehensive research on the role of EEG alpha rhythm during bodily threatening events. Such note of caution is particularly relevant in light of the recent suggestion to manipulate alpha oscillations through non-invasive brain stimulation (Arendsen, Hugh-Jones, & Lloyd, 2018;Hohn, May, & Ploner, 2019) or sensory entrainment (Ecsy, Brown, & Jones, 2018).…”
Section: Discussionmentioning
confidence: 99%